Effectiveness of Interactive Learning and Discovery Learning Models on Student Learning Outcomes and Activities in Environmental Change - Mohamad, Silpian; Katili, Abubakar Sidik; Baderan, Dewi Wahyuni Kyai (Jurnal Pendidikan MIPA, 2023)
This study aims to determine the differences in student learning activities and outcomes in environmental change materials using interactive learning and discovery learning models. The research method used was a quasi-experimental research with a pretest posttest non-equivalent control group design. Retrieval of data using cluster random sampling method. The total sample of 64 students came from class X IPA 3 which applied the interactive learning model and class X IPA 4 which applied the discovery learning model. The results showed that there were differences in student learning activities in the two classes. Information was obtained in the interactive learning class that the learning activity criteria were very good in all aspects observed, while in the discovery learning class there was one aspect that had very good criteria and five other aspects had good criteria. Based on the results of the analysis N-Gain shows that there are differences in student learning outcomes for the two classes observed. In the interactive learning class the N-Gain value reaches 0.70 (high category) in the discovery learning class reaches 0.46 (medium category).Keywords: interactive learning, discovery learning, learning activities, and learning outcomes.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp39-49